Physician Perceptions of Disposition Decision-making for Older Adults in the Emergency Department: A Preliminary Analysis. (December 2020) - Rutkowski, Rachel A.; Salwei, Megan; Barton, Hanna; Wust, Kathryn; Hoonakker, Peter; Brenny-Fitzpatrick, Maria; King, Barbara; Shah, Manish N.; Pulia, Michael S.; Patterson, Brian W.; Dáil, Paula vW.; Smith, Maureen; et al.
Disposition decision-making in the emergency department (ED) is critical to patient safety and quality of care. Disposition decision-making has particularly important implications for older adults who comprise a significant portion of ED visits annually and are vulnerable to suboptimal outcomes throughout ED care transitions. We conducted a secondary inductive content analysis of interviews with ED physicians (N= 11) to explore their perceptions of who they involve in disposition decision-making and what information they use to make disposition decisions for older adults. ED physicians cited 7 roles (5 types of clinicians, patients and families) and 11 information types, both clinical (e.g. test/lab results) and non-clinical (e.g. family's preference). Our preliminary findings represent a key first step toward the development of interventions that promote patient safety and quality of care for older adults in the ED by supporting the cognitive and communicative aspects of disposition decision-making.